Two sides of the same coin: Student justification for or against evolutionary theory - Pratchayapong Yasri; Thanakorn Maleesut (JPBI (Jurnal Pendidikan Biologi Indonesia), 2018)
Students accepting evolution are likely to rely on science as cognitive authority (i.e. science textbooks and science teachers). In contrast, those not accepting are likely to rely on religion as cognitive authority (i.e. religious texts and religious leaders).  A thematic analysis based on existing quantitative and qualitative studies has been carried out in order to propose a theoretical framework for a range of reasons contributing to students' acceptance and rejection of evolutionary theory. This article urges that instruction of evolution is more than the matter of delivering scientific contents. It also deals with personal worldviews influenced by different forms of cognitive authority. It is therefore important to put more emphasis on developing students’ learning skills to critically evaluate which source of information is scientifically appropriate, with full respect to religious belief of individuals.